PENGARUH MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) DALAM KETERAMPILAN MENULIS ISI TEKS BIOGRAFI SISWA KELAS X SMAN 1 TELUKJAMBE TIMUR - Prasasti, Amelia Fahdiniyah; Huri, Daman Huri; Nurhasanah, Een (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
This research aims to determine the influence of the inside outside circle (IOC) learning model on the skills of writing biographical text content for class X SMA Telukjambe Timur students. The research approach used in this research is a quantitative approach, with a research design, namely a quasi experimental design in the form of a nonequivalent control group design. The sampling technique used in this research is nonprobability sampling with purposive sampling. This sampling technique was used based on the researcher's considerations. The samples chosen were class X Science 2 as the experimental class and class X Science 3 as the control class. The instruments used in this research are observation, tests and documentation. Data analysis used in this research is by carrying out normality tests, influence tests and hypothesis tests. The results of this research show that there is a significant influence in the use of the IOC learning model on students' biographical text writing skills. This can be seen from the average value of the experimental class which is higher than the control class. The average pretest score for students in the experimental class was 55.83 which increased to 80.42 in the posttest. The conclusion of this research is that the IOC learning model is effectively used to improve students' biographical text writing skills. Keywoard: writing skills; inside outside circle learning model.